Iterative technique for generating numerical on-axis holograms ofan object on tilted planes using Rayleigh-Sommerfeldapproximation (BISTUA Revista de la Facultad de Ciencias Básicas, 2021)
We present a new iterative technique based on successive field propaga-tion using the Reyleigh-Sommerfeld (RS) approximation, to generateby computer the amplitude on-axis hologram of an object on a tiltedplane. The technique was validated doing optical and computationalreconstruction of the hologram.